Analisis Kemampuan Berpikir Kreatif Matematis Siswa Smp Ditinjau Dari Gaya Kognitif Reflektif, Impulsif, Dan Gender - Maiti, Misratun; Pardi, M. Habib Husnial (Mathematic Education Departement, State Islamic University of Mataram, 2023)
This study aims to analyze the mathematical creative thinking abilities of junior high school students in terms of reflective, impulsive, and gender cognitive styles. The research method is descriptive qualitative, using a purposive sampling technique with 4 students in class VII SMP Negeri 4 Gunungsari as subjects. While the instruments used are the Matching Familiar Figure Test (MFFT) and tests of creative thinking skills. The results showed that subjects who were male with a reflective cognitive style (SRL) met two indicators of creative thinking ability, namely flexibility and elaboration with an average percentage score of mathematical creative thinking ability achieved by SR1 was 58.33% in the creative level category. obtained is quite creative. Female gender subjects with a reflective cognitive style (SRP) fulfill all three indicators in creative thinking skills, namely fluency, flexibility, and elaboration, with an average percentage score of mathematical creative thinking ability achieved by SRP is 91.66% with the creative level category obtained, namely very creative. Male gender subjects with an impulsive cognitive style (SIL) do not meet the indicators of creative thinking abilities. And female gender subjects with impulsive cognitive style (SIP) fulfill two indicators of creative thinking skills, namely flexibility, and elaboration.